Efficacy and safety of the coplanar technique compared to conventional derotation techniques for spinal deformity surgery: a health technology assessment in children adolescents and adults - Azañedo, Diego (2022)
A health technology assessment (HTA) was carried out to critically analyze the evidence on the efficacy and safety of the surgical correction of spinal deformities using the coplanar technique, compared to the conventional derotation techniques, in children, adolescents and adults. A systematic search of the literature was carried out in the PubMed, Cochrane Library and LILACS databases. In addition, a manual search was carried out in the reference lists of the included studies, on Google and on the websites of specialized societies and groups that produce clinical practice guidelines (CPG) and HTA. In addition, we searched ClinicalTrials.gov and the International Clinical Trial Registry Platform (ICTRP) for clinical trial records in progress or not completed. Five documents were selected for evaluation, including two CPG, a randomized clinical trial, and two observational studies. After a critical evaluation of the evidence, it was concluded that both techniques showed a similar efficacy profile in terms of relevant outcomes such as correction of curvatures in the coronal and sagittal planes, quality of life and surgical time. Likewise, the rates of screw malposition, complications and volume of blood loss did not show significant differences between both techniques. However, the profile of  opportunity cost of the systems that allow the application of the coplanar technique is not favorable in the context of the evaluation, due to its high cost concerning conventional systems.